69.7k views
3 votes
Combine and simplify the following radical expresión.

Combine and simplify the following radical expresión.-example-1

2 Answers

5 votes

Answer:

12(3√6)

Explanation:

6(3√12)(3√2)

= 6(3√4√3)(3√2)

= 12(3√3)(3√2)

= 12(3√6)

3 votes

Answer:
12\sqrt[3]{3}

Explanation:

It is important to remember that:

1)
(\sqrt[n]{a})(\sqrt[n]{b})=\sqrt[n]{ab}

2)
\sqrt[n]{a^n} =a^(n)/(n) =a

Knowing this, and given the radical expression
(2\sqrt[3]{12})(3\sqrt[3]{2}), the procedure is:

Solve the multiplication:


(2*3)\sqrt[3]{12*2} = 6\sqrt[3]{24}

Descompose 24 into its prime factors:


24 = 2*2 *2*3 =2^(3)*3

Rewriting the radicand and simplifying, we get:


6\sqrt[3]{2^3*3} = (6)(2)\sqrt[3]{3}= 12\sqrt[3]{3}

User FranCarstens
by
4.8k points